IMPLEMENTASI DATA MINING PADA PENGARUH BRANDING KOPI TERHADAP LOYALITAS KONSUMEN DI DENPASAR - winda patria, ni kadek winda patrianingsih; Astitiani , Ini Luh Putu Surya; Pakpahan, Rahel N (STMIK KAPUTAMA, 2026)
The coffee industry is currently growing very rapidly and has become part of people's lifestyles, especially in urban areas such as Denpasar. This condition has driven increased competition between coffee shops, so the right strategy is needed to retain customers, one of which is through branding. Coffee Shop X, as one of the coffee shops, needs to understand the factors that influence customer loyalty. This study aims to analyze the effect of branding on customer loyalty using a data mining approach. Data was collected from 75 respondents with variables including brand awareness, brand image, brand trust, promotion, product quality, and customer experience. The results of processing using the Naïve Bayes algorithm through the Rapid Miner application showed an accuracy level of 97.30%. These results indicate that the model is able to classify customer loyalty very well and can be used as a basis for strategic decision making.